Politeness Strategies in Mark and Eric Nam’s Podcast on Dive Studios YouTube Channel: A Pragmatic Analysis - Nurmalia, Lia Nurmalia; Fazharani, Rahma (Wanastra: Jurnal Bahasa dan Sastra, 2025)
The objectives of this research are to analyze the use of positive politeness strategies and the number of positive politeness strategies found in Mark and Eric Nam's podcast using the theory of Brown and Levinson. This research is designed using a qualitative descriptive method, which involves explaining the utterances and purpose of the conversation in Mark and Eric Nam's podcast, related to positive politeness strategies. Research data was obtained from the episode of "Mark of NCT 127 Naver Stops Talking, Can Anyone 'Fact Check' This Convo? Twenty-six data points of positive politeness strategies are found on the podcast. The results show, the most frequent politeness strategies are strategy 2: Exaggerate (interest, approval, sympathy with Hearer), 8 data. Strategy 3: Intensify interest in Hearer 6 data. Furthermore, Strategy 5: Seek Agreement 4 data. Strategy 4: Use in-group identity markers 3 data. Strategy 1: Notice, attend to Hearer (interests, wants, needs, goals), 1 data. Strategy 11: Be optimistic 1 data. And then, Strategy 15: Give gifts to Hearer (good, sympathy, understanding, cooperation) 1 data. The most frequent politeness strategy shows how the speakers in that podcast respect each other and keep the conversation on the same point of view.